A review of literature on communication skills development (CSD) in the engineering curriculum - Othman, Rohani; Awang, Zubaidah (2008)
Engineering education has expanded recently to include emphasis on the development of some very specific non-technical attributes that match a strong technical base to produce well-rounded engineering graduates who are flexible and adaptable to suit the constantly developing and changing requirements of the workplace. These non technical skills include communication skills, the ability to function in teams, knowledge of societal and contemporary issues, development of global perspective, and ethics awareness. A great importance of these abilities to engineering education has emerged over the last decade even within the international and local scene. Within the Malaysian context, the Engineering Accreditation Council’s (EAC) Engineering Program Accreditation Manual(BEM, 2007) , outlines ten learning outcomes that encompasses both the technical and non technical skills which are considered essential for graduating engineers. Similarly, the Accreditation Board of Engineering and Technology (ABET) Criterion 3 (ABET, 2000), outlines eleven criterion which targeted many of these as essential program outcomes in order for engineering programs to be accredited and which are seen as critical for the success in the twenty first century. Communication skills development(CSD) is one of the outcomes required by an undergraduate engineering program in the Engineering Accreditation Council (EAC) for Institutions of Higher Learning (IHL) in Malaysia as well as in the ABET Engineering Criteria 2000 (ABET, 2000). CSD is essential for an engineer who aspires to carry out his/her professional practice in the global arena and especially in the English language. With an increasingly global economy, the Malaysian education system must produce graduates who can communicate effectively in English. Otherwise, it would lose one of its vital selling points for foreign investors to ensure that skilled labor force are sufficient to support internationally competitive commerce and industry and to provide individuals with opportunities to optimize their potentials (Muhammad Rashid bin Rajuddin, 2006; Riemer, 2002).